Pengaruh Gaya Kepemimpinan Situasional dan Kepuasan Kerja Terhadap Kinerja Karyawan: Studi Kasus TB. Santia Jaya Karawang - Anggita Wulandari; Suroso; Flora Patricia Anggela (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to examine how situational leadership styles and job satisfaction impact employee performance at TB. Santia Jaya Karawang. The research method employed a quantitative approach involving 60 employees from TB. Santia Jaya Karawang as the study sample, utilizing a saturated sampling technique. Data analysis was conducted using multiple linear regression with F and t-tests, with a significance level of 5%. The research findings indicate that situational leadership style (X1) significantly influences employee performance at TB. Santia Jaya Karawang, with a t-table value (2.735 > 2.002) or t-statistic > t-table. Additionally, it was revealed that job satisfaction (X2) partially affects employee performance at TB. Santia Jaya Karawang, with a t-table value (3.956 > 2.002) or t-statistic > t-table. Overall, situational leadership styles and job satisfaction collectively impact employee performance (Y), as indicated by an F-value of 21.509 > 3.16. Therefore, the combined effect of situational leadership styles and job satisfaction on employee performance at TB. Santia Jaya Karawang is 43%, while the remaining 57% is influenced by other factors not examined in this study.